"Assessment of Wind Speed Distributions and Turbine Characteristics in Equatorial West Africa" (2026)
Wind nullity, low wind, and bi- or multi-modality are common characteristics at high temporal resolution, especially in Equatorial regions. The traditional two-parameter Weibull (Weibull) distribution function (DF) is not designed to capture such peculiarities. Hourly mean wind speed data for eight locations that cut across different climate zones in an Equatorial region of West Africa have been analyzed using Weibull and Maximum Entropy Principle-based (MEP) distribution functions (DFs). Wind characteristics, such as power density, null wind speed, and modal distributions, together with turbine efficiency, capacity, and availability factors, were also assessed at a wind turbine hub height of 73 m using standard statistical tools. The results indicated that null wind speed and/or bimodality were present in the wind distributions at Abuja, Akure, Akungba, Nsukka, Makurdi, and Yola. The results of the assessments of the two DFs show that the MEP DF generated much better results across all time scales (R2: 0.83 - 0.98; RMSE: 0.0037 - 0.0109 m/s2) than the Weibull DF (R2: 0.47 - 0.98; RMSE: 0.0038 - 0.0191 m/s2), especially for locations where null wind speed and bimodality were prominent in the wind data distribution. MEP DF results further indicated that annual and rainy season periods were better modeled than the dry season in all the locations. The overall effect of all the turbine characteristics on annual and seasonal scales is that sufficient winds were available (Availability factor: 0.733 - 0.97; Capacity factor: 0.350 - 0.778) at the rated power for energy production in all the climate zones.